[PP.24.01] SERIAL AMBULATORY BLOOD PRESSURE MONITORING, INTENSITY OF ANTIHYPERTENSIVE DRUG TREATMENT, AND PREGNANCY OUTCOMES IN WOMEN WITH HYPERTENSION FOUND EARLY DURING PREGNANCY. (September 2016) - Gryglas, P.; Jedrusik, P.; Wojciechowska, E.; Gryglas, A.; Dabrowski, M.; Symonides, B.; Gaciong, Z.
Abstract : Objective: Few data are available on serial ambulatory blood pressure monitoring (ABPM) throughout pregnancy and antihypertensive drug treatment required for good blood pressure (BP) control in hypertensive pregnant women. Our aim was to evaluate BP control, antihypertensive drug treatment intensity, and pregnancy outcomes in patients with hypertension (HTN) found early during pregnancy. Design and method: We studied 49 consecutive pregnant patients (mean age 33.4 ± 4.8 years, BMI before pregnancy 24.5 ± 3.7 kg/m 2 ) referred for office HTN found early during pregnancy (mostly before 5 weeks) who gave birth to 50 children (1 twin pregnancy) in 2011–2015. Gestational HTN was previously diagnosed in 39 women, and 9 women had a history of previous miscarriage or stillbirth, with multiple previous pregnancies lost in some patients. ABPM was repeated at 5–10–15–20–25–30–33–35–37 weeks of pregnancy. We calculated overall antihypertensive treatment intensity in standard daily drug doses per patient (standard doses: labetalol 200 mg, methyldopa 750 mg, metoprolol 50 mg, nifedipine 20 mg, verapamil 120 mg). Statistical analysis was performed using ANOVA. Results: All children were born alive (24 vaginal delivery, 26 cesarean section) and are well at follow-up. Gestational age was 38.0 ± 2.5 (range 29–40) weeks, and birth weight was 3215 ± 653 g (range 955–4200). Preeclampsia/eclampsia occurred in 10/3 patients. Four patients had normal BP values by ABPM throughout pregnancy and did not receive antihypertensive drugs. Most patients were treated with labetalol (100–600 mg) and methyldopa (500–2000 mg). Throughout pregnancy, BP remained well controlled (24 h mean SBP/DBP 120.3–126.0/75.3–77.1 mmHg), the number of treated patients increased from 25 at 5 weeks to 42 at 25–35 weeks, and the average number of daily antihypertensive drug doses in treated pts increased from 1.82 at 5 weeks to 2.98 at 37 weeks (p < 0.001). Figure. No caption available. Conclusions: Serial ABPM-guided antihypertensive drug treatment started early during pregnancy was associated with favorable outcomes. The number of patients requiring treatment and the treatment intensity to maintain good BP control increased throughout the pregnancy. No physiological BP fall at the end of 1st trimester was observed. Our findings help estimate the expected treatment intensity required in pregnant patients with preexisting hypertension.